Successful treatment with nilotinib after bosutinib-induced pulmonary arterial hypertension recurrence following dasatinib in chronic myeloid leukemia in chronic phase. (2022) - Takatsuka, Ibuki; Hirata, Hiroya; Takahashi, Takumi; Dohtan, Satoshi; Oka, Shinichiro; Sakamoto, Nami; Takaba, Masamitsu; Adachi, Miwa; Takemura, Tomonari; Nagata, Yasuyuki; Ono, Takaaki
Highlights: Pulmonary arterial hypertension (PAH) is the lethal adverse event of dasatinib. We experienced bosutinib-induced PAH recurrence following dasatinib. Treatment response without PAH recurrence was obtained by switching to nilotinib. Abstract: A 52-year-old man was diagnosed with chronic myeloid leukemia in the chronic phase (CML-CP). He experienced bosutinib-induced pulmonary arterial hypertension (PAH) recurrence following dasatinib use. Symptoms and examination findings associated with PAH improved after bosutinib cessation. Although nilotinib was started because of the loss of response after bosutinib cessation, a deep molecular response without PAH recurrence was achieved 3 months after the initiation of nilotinib therapy. PAH recurrence after switching to bosutinib due to dasatinib-induced PAH should be closely monitored. In addition, nilotinib therapy might be an effective approach in PAH cases related to dasatinib and/or bosutinib in patients with CML-CP.